Land Reform Policy in Determining Abandoned Land for Halal Tourism Destination Management Based on Fiqh Siyasah - Jaelani, Abdul Kadir; Rabbani, Anila; Hayat, Muhammad Jihadul (El-Mashlahah, 2024)
The government has established a policy of utilizing abandoned land to develop halal tourism. However, the critical question is whether this policy, based on siyasah fiqh, impacts Indonesia's economic development. The research analyzed land reform policies, which determine abandoned land for managing halal tourism destinations based on Fiqh siyasah. This study employed normative legal studies and secondary data. The research indicated that the use of abandoned land for halal tourism development is not grounded in Islamic jurisprudence, and it potentially violates the provisions of Article 27 paragraph (2) and Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia, leading to violations of human rights.